Acute Sickle Hepatic Crisis after Liver Transplantation in a Patient with Hb SC Disease - J. H. Gillis; S. K. Satapathy; L. Parsa; P. B. Sylvestre; N. Dbouk (Case Reports in Transplantation)
Acute sickle hepatic crisis (ASHC) has been observed in approximately 10% of patients with sickle cell disease. It occurs predominantly in patients with homozygous (Hb SS) sickle cell anemia and to a lesser degree in patients with Hb SC disease, sickle cell trait, and Hb S beta thalassemia. Patients commonly present with jaundice, right upper quadrant pain, nausea, low-grade fever, tender hepatomegaly, and mild to moderate elevations in serum AST, ALT, and bilirubin. We describe the case of a patient with a history of hemoglobin SC disease and cirrhosis caused by hepatitis C presenting approximately 1 year after liver transplantation with an ASHC. The diagnosis was confirmed by liver biopsy. Our patient was treated with RBC exchange transfusions, IV hydration, and analgesia and made a complete recovery. Only a limited number of patients with sickle cell disease have received liver transplants, and, to our knowledge, this is the first case of ASHC after transplantation in a patient with Hb SC disease.